Sustainability in formal Education: ways to integrate it now - Agueda Gras-Velazquez; Verdiana Fronza (IUL Research)
Sustainability emerged as a way to address global challenges “without leaving anyone behind”. Nevertheless, sustainability is hard to implement. At the individual level, education can help,  as recognised at the international level. This paper looks at sustainability for education, and vice versa to decipher why the two benefit from each other. Education fosters literacy, forming the citizens of tomorrow: it can thus support sustainability, promoting a positive understanding of nature among students. Thanks to its interdisciplinary nature, sustainability can foster collaboration among different subjects and offer new practices helping education to prepare students for a complex future. This interplay can exist without intervening in the national curricula, by focussing on student-centred pedagogies, and the role of teachers. Three projects show how, through learning scenarios, massive online open courses and competitions, teachers can support sustainability education. Hence, this paper shows that the integration of sustainability in education is recommendable and achievable.